Neuroticism Is Associated with Chronic Severe Pain among Ex-Opioid Users on Methadone Maintenance Therapy - Chin, Hong Koh; Othman, Zahiruddin (Japan International Cultural Exchange Foundation, 2019)
Introduction: Among ex-opioid users on methadone maintenance therapy (MMT), the prevalence of chronic severe pain (CSP) was reported as 37-48.2%. The CSP causes distress, adversely affects quality of life, addiction treatment outcome and exacerbates patients ambivalence towards MMT. Neuroticism personality trait is associated with CSP, but the similar association has yet to be explored in ex-opioid users on MMT. Objectives: This study aims to determine the prevalence of CSP among ex-opioid users on MMT, and to examine whether neuroticism is significantly associated with CSP. Methods: In this cross-sectional study, validated Malay version of big five inventory (BFI), brief pain inventory (BPI), Beck's depression inventory (BDI), and Beck's anxiety inventory (BAI) were utilized for measurement of neuroticism, pain, depression and anxiety symptoms, respectively. Subjects were recruited from two MMT centres in Alor Star, Malaysia. Results: A total of 151 subjects were recruited, consisting of 104 from Klinik Kesihatan Bandar Alor Setar, and 47 from Hospital Sultanah Bahiyah. The prevalence of CSP, regular use of over-the-counter (OTC) analgesics and kratom product were 22.5%, 28.5%, and 40.4%, respectively. Using multiple logistic regression analyses, neuroticism score (p < 0.001), BAI score (p = 0.012) and regular OTC analgesic use (p = 0.016) were found to be statistically significant in association with CSP, with adjusted odds ratio of 1.60 (95% CI 1.27, 2.12), 1.44 (95% CI 1.08, 1.93), and 3.56 (95% CI 1.27, 10.01), respectively. Conclusion: Neuroticism, anxiety and regular use of OTC analgesics were independently associated with CSP among ex-opioid users on MMT. Otherwise, no significant association was observed for depression, HIV status, regular use of kratom, and other socio-demographic or clinical characteristics.